2022
DOI: 10.3390/cleantechnol4010012
|View full text |Cite
|
Sign up to set email alerts
|

The Energy Efficiency Post-COVID-19 in China’s Office Buildings

Abstract: China promptly took the leading step to mitigate the spread of COVID-19, producing the first scientific guidelines assuming health above energy consumption and significantly changing HVAC/AHU operation. The research intended to fulfill the gap by measuring the impact of the guidelines on energy use intensity, CO2 emissions, and energy operation costs related to workplaces. The guidelines are long-term sector and industry trends following occupants’ health and safety concerns, and today they are applied to nurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…These workers value this perk because they believe it will help them strike a better balance between their personal and professional lives. Telecommuting and other hybrid work models have an impact, reducing building occupancy and posing new questions about the optimal use of office space and the associated environmental impacts, as reported by (Duarte and Cortiços, 2022).…”
Section: Occupa Onmentioning
confidence: 99%
“…These workers value this perk because they believe it will help them strike a better balance between their personal and professional lives. Telecommuting and other hybrid work models have an impact, reducing building occupancy and posing new questions about the optimal use of office space and the associated environmental impacts, as reported by (Duarte and Cortiços, 2022).…”
Section: Occupa Onmentioning
confidence: 99%
“…Temporary bans were imposed on all foreign passengers who had recently visited the hardest-hit regions within the previous 14 days. The infectious disease outbreaks stemming from COVID-19 have had a substantial impact, resulting in significant disease burdens, increased energy consumption, and economic challenges for affected countries [1,2]. To minimize the spread of the pandemic, countries have swiftly adapted their flight adjustment policies in response to changing pandemic dynamics, necessitating frequent modifications of flight schedules.…”
Section: Introductionmentioning
confidence: 99%
“…Rouleau and Gosselin [21] found a 46% increase in electricity use in social housing in Canada during the lockdown period. Duarte and Cortiços [22] performed energy simulations in office buildings in China under the post-COVID-19 scenarios, resulting in an upward and downward trend based on the climate zones. Su et al [23] compared the energy consumption pattern and indoor air quality of a large green commercial building in China and reported that the building energy consumption decreased by an average of 55.4% and the indoor air quality compliance rate increased.…”
Section: Introductionmentioning
confidence: 99%